2009
DOI: 10.1111/j.1447-0756.2009.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the knowledge and attitudes of pregnant Thai women towards Down syndrome screening

Abstract: Most pregnant women had inadequate knowledge of Down syndrome and the screening test. However, they did have a positive attitude and were willing to accept the test. Providing knowledge on Down syndrome and the screening test for pregnant women should be implemented in our antenatal care services and community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 7 publications
(13 reference statements)
3
26
0
Order By: Relevance
“…Screening tests have now been improved through biochemical tests and ultrasound screening and they are now implemented in many parts of the world (Mulley & Wallace , Pruksanusak et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Screening tests have now been improved through biochemical tests and ultrasound screening and they are now implemented in many parts of the world (Mulley & Wallace , Pruksanusak et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…This is in contrast to another study which showed that higher education positively affected the knowledge of DS. 15 There was no correlation between the parity and age, with knowledge. 16 When we considered women with family history of Down syndrome and previous baby with Down syndrome we found that eight of the 12 women (66.6%) had good knowledge of Down syndrome and 9 out of the 15 women (60%) in women with previous history of Down syndrome had good knowledge of DS, but the methods available for screening was still not well understood.…”
mentioning
confidence: 99%
“…() noted that there was evidence of a lack of acceptance of children with DS by parents and wider society, and Pruksanusak et al . () indicated that Thai women were mostly unsure if they could accept having a baby with DS. However, in healthcare practice, balanced and unbiased information should be provided to women in order to promote concept of non‐directiveness.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Pruksanusak et al . () found Thai women mostly had poor knowledge about DSS tests, especially interpretation of the screening tests. In addition to the purpose of the screening tests, the limitations of such tests should be emphasized.…”
Section: Discussionmentioning
confidence: 99%